KINERJA PELAYANAN PERIZINAN TERPADU - Aulia Kharisma; Meyzi Heriyanto; Chalid Sahuri (Universitas Riau, 2018)
Performance of Integrated Licensing Services. The study aims to find out how the performance of integrated licensing services in Pelalawan Kabupten as well as to know what constraints faced. Methods in this study using qualitative, ie data obtained in the form of interviews and questionnaires processed through qualitative data analysis. In general, this study can be concluded that the Analysis of Service Performance in Integrated Licensing Service Office and Capital Investment of Pelalawan District The success of permit service at Pelalawan District's Integrated Licensing Service and Licensing Service (BPMP2T) has been